Diseño de software médico para manejo de los datos de la historia clínica ocupacional, en una empresa petrolera, durante el periodo enero-mayo 2014 - Ordóñez León, Laura Melissa (2015)
This project was developed to facilitate the data management of Occupational Health Records for an oil company, which owns six Medical Clinics, located in Quito and the Ecuadorian Oriente. The development of this medical software is based on safety of Ecuador and health legislation in force and integrates the Human Resources, Safety and Health departments in monitoring the health of workers. This project met its objectives by facilitating access to and organization of medical information, and by this way, allowing the possibility to contrast and compare medical data of health surveillance programs and the control of the budget allocated to the health area. It also supplies databases for analysis and research, as well as the development of proposals in preventive and curative health, and the monitoring of workers risks and occupational diseases.